2018
DOI: 10.1155/2018/3053704
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐Induced Reductive Stress Is a Protective Mechanism against Oxidative Stress in Peripheral Blood Mononuclear Cells

Abstract: Eccentric exercise is a well-studied modality that induces oxidative stress and muscle damage. Furthermore, it promotes inflammatory response in which peripheral blood mononuclear cells (PBMCs) are the major mediators. Although free radicals are necessary in a specific range of concentrations, yet unknown, it remains unclear whether reductive redox status (i.e., increased antioxidant defenses and impaired free radical generation) is beneficial or not. Thus, the aim of the present investigation was to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 41 publications
0
22
0
1
Order By: Relevance
“…In addition, we also analyzed the role of GSH baseline values on the effects of fasting. This could be an important issue since the therapeutic efficiency of any redox-altering intervention depends on the baseline levels of endogenous antioxidants, also called antioxidant status [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we also analyzed the role of GSH baseline values on the effects of fasting. This could be an important issue since the therapeutic efficiency of any redox-altering intervention depends on the baseline levels of endogenous antioxidants, also called antioxidant status [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude that the cut-off at ten days does not reflect the changes in all subjects. Furthermore, the reductive stress induced by exercise, although generally known to be beneficial, can be detrimental for individuals with low GSH values, but not for those individuals with increased baseline GSH values [ 36 ]. The effects of redox-altering stimuli, such as antioxidant administration and exercise, on blood redox status, are highly dependent on the baseline values of the intrinsic antioxidant mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise is a known strategy to modulate levels of OS in older adults, but the relationship between exercise and OS is extremely complex, depending on the mode, intensity, and duration of exercise. Studies have shown that regular exercise with light to moderate intensity could gradually strengthen endogenic antioxidant defense mechanism and diminish level of OS (De Sousa et al, 2017;Spanidis et al, 2018). Conversely, acute exercise and high-intensity exercise lead to increased level of OS (Pingitore et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, exercise training induces an increased activity of mitochondrial 8-oxoguanine DNA glycosylase (OGG1), which is responsible for the excision of the mutagenic base byproduct 8-oxoguanine, in the nuclei of red fibers but a decreased activity in nuclei of white fibers [33]. Interestingly, the protective effects of exercise have been reported not only in skeletal muscle [34,35] but also in the liver [36,37], kidney [38], brain [39,40,41], and blood [42,43]. Regarding the protective potential of training on blood cells, DNA damage is lower in peripheral blood mononuclear cells of trained individuals compared to untrained individuals after exposure to oxidative stress [12].…”
Section: Introductionmentioning
confidence: 99%